STRENGTHENING THERAPEUTIC REGIMEN IN FAMILIES WITH ODGJ IN THE TODO HEALTH CENTER WORK AREA - Beo, Yosef Andrian; Fariday Dewi, Claudia; Jakri, John (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The condition of People with Mental Disorders (ODGJ) is a serious public health problem and requires special attention. Proper treatment and good family support are important factors in recovery and improved quality of life for individuals with ODGJ. Community service in strengthening therapeutic regimens for families with ODGJ in the Todo Health Center work area aims to improve family understanding and skills in caring for and supporting family members who experience ODGJ. This service is carried out through a series of activities, including counseling, training, and mentoring families with ODGJ for a certain period. The results of this service show an increase in family understanding of ODGJ, including trigger factors, symptoms, and appropriate actions in responding to crisis situations. In addition, families are also trained in adhering to therapeutic regimens prescribed by medical personnel, including regular medication timing and healthy lifestyles for family members with ODGJ. The results of the evaluation showed an improvement in the quality of life of family members with ODGJ, where they more actively participated in social activities and were able to manage stress arising from ODGJ conditions. In addition, there is also an increase in adherence to the therapeutic regimen he undergoes, so that the use of drugs becomes more consistent and effective.